STUDIES ON RADIATION PASTEURISATION OF MEDIUM FATTY FISH III. STORAGE PROPERTIES OF WHITE POMFRET(Stromateus cinereus ) FILLETS - KAMAT, S V; GAONKAR, S. G; KUMTA, U S (Fishery Technology, 2025)
White pomfret fillets packed under aerobic conditions had a limited shelf life of 8 days as against 10 days for samples packed under vacuum and stored at 0 2Â°C. Irradiation and subsequent storage of the fillets under vacuum at 0-2Â°C exhibited shelf lives of 30, 50 and 60 days for radiation doses of 0.1, 0.3 and 0.5 Mrad respectively in contrast to aerobically packed fillets which showed only 20, 35 and 50 days of storage life for the same levels of radiation doses and developed yellow discolouration and rancid odours.